# Problem of the Week

## Updated at Oct 28, 2019 12:04 PM

To get more practice in equation, we brought you this problem of the week:

How would you solve the equation $$3(x-3)(4x+4)=60$$?

Check out the solution below!

$3(x-3)(4x+4)=60$

 1 Expand.$12{x}^{2}+12x-36x-36=60$2 Simplify  $$12{x}^{2}+12x-36x-36$$  to  $$12{x}^{2}-24x-36$$.$12{x}^{2}-24x-36=60$3 Move all terms to one side.$12{x}^{2}-24x-36-60=0$4 Simplify  $$12{x}^{2}-24x-36-60$$  to  $$12{x}^{2}-24x-96$$.$12{x}^{2}-24x-96=0$5 Factor out the common term $$12$$.$12({x}^{2}-2x-8)=0$6 Factor $${x}^{2}-2x-8$$.1 Ask: Which two numbers add up to $$-2$$ and multiply to $$-8$$?$$-4$$ and $$2$$2 Rewrite the expression using the above.$(x-4)(x+2)$To get access to all 'How?' and 'Why?' steps, join Cymath Plus!$12(x-4)(x+2)=0$7 Solve for $$x$$.1 Ask: When will $$(x-4)(x+2)$$ equal zero?When $$x-4=0$$ or $$x+2=0$$2 Solve each of the 2 equations above.$x=4,-2$To get access to all 'How?' and 'Why?' steps, join Cymath Plus!$x=4,-2$Done x=4,-2